Fifteen‐year trends in the management of cardiogenic shock and associated 1‐year mortality in elderly patients with acute myocardial infarction: the FAST‐MI programme. (September 2016) - Aissaoui, Nadia; Puymirat, Etienne; Juilliere, Yves; Jourdain, Patrick; Blanchard, Didier; Schiele, François; Guéret, Pascal; Popovic, Batric; Ferrieres, Jean; Simon, Tabassome; Danchin, Nicolas
Abstract: Aims: Alhough cardiogenic shock (CS) after acute myocardial infarction (AMI) is more common in elderly patients, information on the epidemiology of these patients is scarce. This study aimed to assess the trends in prevalence, characteristics, management, and outcomes of elderly patients admitted with CS complicating AMI between 1995 and 2010, using data from the FAST‐MI programme. Methods and results: We analysed the incidence and 1‐year mortality of CS in four nationwide French surveys carried out 5 years apart from 1995 to 2010, including consecutive AMI patients over 1‐month periods. Among the 10 610 patients, 3389 were aged ≥75 years, of whom 9.9% developed CS. The prevalence of CS decreased in elderly patients from 11.6% in 1995 to 6.7% in 2010 ( P = 0.02). Over the 15‐year period, the characteristics of elderly patients with CS changed, with more diabetes, hypertension, and hypercholesterolaemia. The use of PCI increased markedly in elderly patients with and without CS, reaching 51% and 59%, respectively, in 2010. In addition, medical therapy also evolved, with more patients receiving antithrombotic agents, beta‐blockers, and statins. Over time, 1‐year mortality decreased by 32% among elderly patients with CS but remained high (59% in 2010). ST‐segmet elevation myocardial infarction and previous AMI were independent correlates of increased 1‐year death, while study period was associated with decreased mortality (2010 vs, 1995: hazard ratio 0.40, 95% confidence interval 0.27–0.61, P < 0.001), along with early use of PCI. Conclusion: Cardiogenic shock in elderly patients with AMI remains a major clinical concern. However, 1‐year mortality declined in these patients, a decrease potentially mediated by broader use of PCI and the improvement of global patient management.